Spatial Distribution of the Input of Insoluble Particles Into the Surface of the Qaanaaq Glacier, Northwestern Greenland - Matoba, Sumito; Hazuki, Ryo; Kurosaki, Yutaka; Aoki, Teruo (Frontiers in Earth Science, 2020)
From glaciological observations, we found spatial variation in the input of insoluble particles (ISP) on a glacier surface from atmospheric deposition and outcropping from the inside of the glacier at the ablation zone of the Qaanaaq Ice Cap in northwestern Greenland. Possible sources of ISP input to the glacier surface were outcropping from inside of the glacier at intermediate and low elevations, and from atmospheric deposition at high elevations. The annual atmospheric deposition of ISP was larger at high elevations than at intermediate and low elevations. The annual abundance of outcropping ISP was larger at intermediate elevations than at low elevations, where the annual ablation rate of the glacier surface was 1.5 times larger than at intermediate elevations. The ISP concentration inside of the glacier at intermediate sites was approximately 10 times larger than at low sites. The water stable isotopes of glacier ice at intermediate sites indicated that glacier ice at the intermediate sites did not form since the last glacial maximum, possibly the Holocene Thermal Maximum. Therefore, accumulation of the ISP, which is outcropping at the intermediate site, occurred at high elevations after Holocene Thermal Maximum.